Corrosion behaviour on powder metallurgy aluminium matrix composite reinforced with alumina Saffil™ short fibres - Normah, Cheman (Universiti Malaysia Perlis, 2010)
The corrosion behaviour of PM Al composite will be affected by the presence of alloying element and reinforcing phase in the composite. This studies were focused on the influence of magnesium addition and alumina Saffil™ short fibres reinforcement on corrosion behaviour of PM AMCs. PM Al composite and PM Al-Mg composite were fabricated from flaky aluminium powder, granular magnesium and alumina Saffil™ short fibres with an average particle size of 70.58 µm, 273.41 µm and 16.71 μm, respectively. The experimental parameter were maintained the content of magnesium powder (ranging from 0.5 wt% to 3.0 wt%) and alumina Saffil™ short fibres (ranging from 5 wt% to 25 wt%) . The samples were fabricated by using 200 MPa uniaxial pressing and sintered in argon atmosphera for 6 hours. Sintered samples were characterized by using SEM, density and porosity analysis and Vickers hardness testing. The optimum samples were tested in corrosion properties by using electrochemical test and immersion test. Both experiment using 3.5 wt% NaCl as corrosion environment. Electrochemical test was carried out with apply potentiostat Gamry G300 to create Tafel plot and polarization curve. The immersion test was carried out for 28, 56 and 84 days. Weight loss curves were acquired from immersion test results. Photomicrographs of samples were examined using scanning electron microscopy (SEM). The elemental composition of sample was analyzed by Energy dispersive X-ray (EDX) analysis. The presence of an oxide phases were verified by X-ray diffraction analysis (XRD). Experimental results showed the wetability between alumina Saffil™ short fibres and Al matrix have been improved by adding magnesium in the PM Al composite. PM Al – 15 wt% Al2O3 and PM Al – 2 wt% Mg - 15 wt% Al2O3 were identified as the optimum sample. The corrosion rate of PM Al composite was decreased from 67.69 µm/year to 0.66 µm/year when 2 wt% of magnesium was added in PM Al-Mg composite. SEM photomicrograph observed that pitting was localized surrounding the magnesium constituents which occur randomly throughout the surface of PM Al-Mg composite. XRD analysis revealed that aluminum oxide (δ-Al Al1.67O4), aluminium hydroxide (Al (OH)3) and aluminium oxide (α-Al2O3) phases were detected in oxide film. The critical current density (Icrit) of PM Al composite is lower than PM Al-Mg composite which is 2.0 x 10-1 A/cm2 and 4.0 x10-1 A/cm2, respectively. Magnesium is used as inhibitor in corrosion behaviour of PM Al-Mg composite have been changed and protected with a stable formation of oxide film. The corrosion resistance of PM Al-composite was decreased with the presence of alumina Saffil™ short fibres in composite due to discontinuities in oxide film provided the corrosion initiated in sample.